Input Efficiency of Financial Services Sector: A Non-parametric analysis of Banking and Insurance Sectors of Pakistan - Shah, Syed Alamdar Ali; Masood, Dr. Omar (European Journal of Islamic Finance, 2017)
Purpose In an attempt to enrich the literature of the efficiency of financial services sector with holistic perspective, this study aims to empirically investigate the input efficiency of banking and insurance sectors with further probe into Islamic segments of these sectors in Pakistan. Design/methodology/approach This study measures the technical, allocative, cost, and scale efficiencies of banking and insurance firms in our sample using the non-parametric frontier method, data envelopment analysis (DEA). Findings The findings show that, on average, the allocative efficiency of the overall Islamic financial services sector has increased during the period of study and has also remained well above their conventional counterparts. The study also revealed that, insurance sector is more technically efficient than banking sector. Finally, the study also found that overall efficiency of financial sector can also be improved by exchanging experts between two sectors. Originality/value The results of this research study provide empirical findings as to how two segments of Financial Services Sectors had fared in the competitive environment from 2007 to 2015.